Advances in Degradable Embolic Microspheres: A State of the Art Review - Jensen Doucet; Lauren Kiri; Kathleen O’Connell; Sharon Kehoe; Robert J. Lewandowski; David M. Liu; Robert J. Abraham; Daniel Boyd (Journal of Functional Biomaterials, 2018)
Considerable efforts have been placed on the development of degradable microspheres for use in transarterial embolization indications. Using the guidance of the U.S. Food and Drug Administration (FDA) special controls document for the preclinical evaluation of vascular embolization devices, this review consolidates all relevant data pertaining to novel degradable microsphere technologies for bland embolization into a single reference. This review emphasizes intended use, chemical composition, degradative mechanisms, and pre-clinical safety, efficacy, and performance, while summarizing the key advantages and disadvantages for each degradable technology that is currently under development for transarterial embolization. This review is intended to provide an inclusive reference for clinicians that may facilitate an understanding of clinical and technical concepts related to this field of interventional radiology. For materials scientists, this review highlights innovative devices and current evaluation methodologies (i.e., preclinical models), and is designed to be instructive in the development of innovative/new technologies and evaluation methodologies.